Impact of interferon‐free regimens on the glomerular filtration rate during treatment of chronic hepatitis C in a real‐life cohort. Issue 6 (27th February 2018) - Álvarez‐Ossorio, M. J.; Sarmento e Castro, R.; Granados, R.; Macías, J.; Morano‐Amado, L. E.; Ríos, M. J.; Merino, D.; Álvarez, E. N.; Collado, A.; Pérez‐Pérez, M.; Téllez, F.; Martín, J. M.; et al.
Summary: Little data are available on renal toxicity exerted by direct‐acting antivirals (DAAs) in real life. The aim of this study was to assess the impact of direct‐acting antivirals against hepatitis C virus infection currently used in Spain and Portugal on the estimated glomerular filtration rate (eGFR) in clinical practise. From an international, prospective multicohort study, patients treated with DAAs for at least 12 weeks and with eGFR ≥30 mL/min per 1.73 m 2 at baseline were selected. eGFR was determined using the CKD‐EPI formula. A total of 1131 patients were included; 658 (58%) were HIV/HCV‐coinfected patients. Among the 901 patients treated for 12 weeks, median (interquartile range) eGFR was 100 (87‐107) at baseline vs 97 (85‐105) mL/min per 1.73 m 2 at week 12 of follow‐up (FU12) post‐treatment ( P < .001). For HIV‐coinfected subjects who received tenofovir plus a ritonavir‐boosted HIV protease inhibitor (PI/r), baseline vs FU12 eGFR were 104 (86‐109) vs 104 (91‐110) mL/min per 1.73 m 2 ( P = .913). Among subjects receiving ombitasvir/paritaprevir with or without dasabuvir, eGFR did not show any significant change. Of 1100 subjects with eGFR >60 mL/min per 1.73 m 2 at baseline, 22 (2%) had eGFR <60 mL/min per 1.73 m 2 at FU12, but none presented with eGFR <30 mL/min per 1.73 m 2 . In conclusion, eGFR slightly declines during therapy with all‐oral DAAs and this effect persists up to 12 weeks after stopping treatment in subjects with normal to moderately impaired renal function, regardless of HIV status. Concomitant use of tenofovir plus PI/r does not seem to have an impact on eGFR.